Auditing human resources management - Dolenko, Marilyn (Institute of Internal Auditors Research Foundation Altamonte SpringsUS, 1990)
Provides background information on personnel functions, suggests standards or criteria against which personnel systems and activities can be measured. Contains suggestions on how auditors can help managers make the best use of their most important resource.